Educational Values on Dendang Saluang Pauah in the Life of the Kuranji Community, Padang City - Caecilia Trisani Lumbantoruan; Syeilendra Syeilendra (Tonika: Jurnal Penelitian dan Pengkajian Seni, 2022)
This study aimed to describe and analyze the educational values ​​contained in the poems and stories of Kaba and the community’s understanding of the aesthetics of Dendang Pauah in the Kuranji District. The presentation of the story of Kaba was a story about the life of community behavior that contained an educational value, also to find out the relationship of the story of Kaba in the performance of Dendang Pauah. The type of research was qualitative research with a descriptive analysis approach. The informants of this study are pemain saluang (flautist), tukang dendang (thugs) and the audience ( old and young age) and other community leaders. The data collection techniques were literature study, observation, interviews and documentation. Ensuring the validity of the data obtained, the data was carefully examined and analyzed using data reduction, presentation, and conclusion. The results of this research showed that the story of Kaba can be proven that the Kuranji guided by the expression of Kaba to live a wise life in the attitude to act, prioritize cooperation with neighbors, gotong royong (mutual assistance) by emphasizing the value of beauty/ aesthetics contained in the presentation of Dendang Saluang Pauah. The tukang Kaba tells the story resounding in the rhythm of a pakok limo song Tanjuang Karang and pakok anam with the pado-pado song then closed with lambok malam rhythm with malereang.